2013
DOI: 10.1063/1.4804794
|View full text |Cite
|
Sign up to set email alerts
|

FAME-C: Retrieval of cloud top pressure with vertically inhomogeneous cloud profiles

Abstract: Abstract.A synergistic FAME-C (Freie Universität Berlin AATSR-MERIS Cloud Retrieval) algorithm is developed within the frame of the ESA CCI Cloud project. Within FAME-C the ratio of two MERIS measurements (the Oxygen-A absorption channel and a window channel) is used to retrieve cloud top pressure. In case of high, extended clouds the retrieved cloud top pressure is generally too high. This can be understood as an overestimation of extinction in upper cloud layers due to the assumption of vertical homogeneous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For two case studies with vertically extended clouds it was shown that the choice of the cloud vertical extinction profile can have a large impact on the retrieved MERIS cloud-top pressure. Comparisons to CPR cloud heights showed that on average the bias was reduced by a large amount when using the mean CPR-profiles instead of vertically homogeneous profiles (HOM) (Henken et al, 2013). This can be mainly attributed to lower extinction values in the upper cloud layers for the CPR-profiles than for the HOM profiles, which appears to be closer to reality for these vertically extended clouds.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For two case studies with vertically extended clouds it was shown that the choice of the cloud vertical extinction profile can have a large impact on the retrieved MERIS cloud-top pressure. Comparisons to CPR cloud heights showed that on average the bias was reduced by a large amount when using the mean CPR-profiles instead of vertically homogeneous profiles (HOM) (Henken et al, 2013). This can be mainly attributed to lower extinction values in the upper cloud layers for the CPR-profiles than for the HOM profiles, which appears to be closer to reality for these vertically extended clouds.…”
Section: Introductionmentioning
confidence: 90%
“…Since the vertical extent is fixed, no further assumption on the CGT in the forward model are needed for these profiles. More details on the resulting profiles and their incorporation into the FAME-C algorithm can be found in Henken et al (2013) and Carbajal Henken et al (2014). The derived normalized extinction profiles (from here on called CPR-profiles/clouds) were then used in the MOMO radiative transfer simulations to generate look-up tables (LUTs) for each of the nine cloud types.…”
Section: Sensitivity Studymentioning
confidence: 99%
“…This increase depends on the vertical extinction profile of the cloud. To derive "realistic" cloud vertical extinction profiles for nine cloud types based on the ISCCP cloud classification (ISCCP), 1 year (2010) of layer optical thicknesses as provided by the CloudSat database is used as described in Henken et al (2013). The geometrical thickness of each cloud type, i.e., the number of adjacent cloud layers with a thickness of 20 hPa, is taken constant and based on an empirical analysis of a number of CloudSat scenes.…”
Section: Meris Cloud Top Pressurementioning
confidence: 99%